A growing concern: How soon will India run out of water? - Rajmohan Panda (Edinburgh University Global Health Society, 2011)
Provision of clean drinking water, sanitation, and a clean environment are vital to improve the health of our people and to reduce incidence of diseases and deaths. India faces a tumultuous water future, and unless remedial measures are taken India's demand for water will exceed all its sources of supply within the next fifteen years. This short supply and scarcity will have a negative effect on public health and sanitation and regress the gains achieved.